2013
DOI: 10.1155/2013/604787
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antiproliferative, and Antiangiogenesis Effects of Polyphenol-Rich Seaweed (Sargassum muticum)

Abstract: In the present study, we evaluated the effect of brown seaweeds Sargassum muticum methanolic extract (SMME), against MCF-7 and MDA-MB-231 breast cancer cell lines proliferation. This algae extract was also evaluated for reducing activity and total polyphenol content. The MTT assay results indicated that the extracts were cytotoxic against breast cancer cell lines in a dose-dependent manner, with IC50 of 22 μg/ml for MCF-7 and 55 μg/ml for MDA-MB-231 cell lines. The percentages of apoptotic MCF-7-treated cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 38 publications
5
99
0
5
Order By: Relevance
“…Even though marine endophytes are studied for antioxidant, cytotoxic and pharmacological potential; much information was not available for the antiangiogenic activity. C. cladosporioides extract showed similar results as that of another fungus ( P.citrinum ) isolated from S. weightii as well as the activity of terrestrial and seaweed endophytes reported earlier (Ben et al 2009; Udagawa et al 2000; Namvar et al 2013; Manjunath et al 2016). …”
Section: Discussionsupporting
confidence: 82%
“…Even though marine endophytes are studied for antioxidant, cytotoxic and pharmacological potential; much information was not available for the antiangiogenic activity. C. cladosporioides extract showed similar results as that of another fungus ( P.citrinum ) isolated from S. weightii as well as the activity of terrestrial and seaweed endophytes reported earlier (Ben et al 2009; Udagawa et al 2000; Namvar et al 2013; Manjunath et al 2016). …”
Section: Discussionsupporting
confidence: 82%
“…Dalton's Ascitic lymphoma, HepG2, HT-29, Ca co-2, T47D, MDA-MB468 and /NIH 313, [55][56][57][58][59][60] Stypopodium sp SH-SY5Y, RBL-2H3, (Raw267), (V79), Caco-2. DU-145 [53,62] Undaria sp is one of the important genera under Pheophyceae.…”
Section: Solieriamentioning
confidence: 99%
“…Ekstrak metanol S. muticum memiliki aktivitas sitotoksik terhadap sel kanker payudara MCF-7 dan MDA-MB-231 dengan nilai IC 50 sebesar 22,0 µg/ml dan 55,0 µg/ml (Namvar et al, 2013). Khanavi et al (2010) memperlihatkan bahwa ekstrak metanol S.swartzii memiliki nilai IC 50 sebesar 205,2 µg/ml terhadap sel T47D sedangkan fraksi n-heksana memiliki nilai IC 50 sebesar 99,9 µg/ml terhadap sel Caco-2.…”
Section: Uji Sitotoksik Ekstrak Aseton Sargassum Dengan Metode Mttunclassified